Functional components of Chinese rice wine can ameliorate diabetic cardiomyopathy through the modulation of autophagy, apoptosis, gut microbiota, and metabolites - Yang, Jinjin; Song, Jiaoying; Zhou, Jiedong; Lin, Hui; Wu, Zhuonan; Liu, Nan; Xie, Wenqing; Guo, Hangyuan; Chi, Jufang (Frontiers in Cardiovascular Medicine, 2022)
Background: Dietary polyphenols, polypeptides, and oligosaccharides modulate inflammation and immunity by altering the composition of gut microbiota. The polyphenols and polypeptides in Chinese rice wine have protective effects against cardiovascular disease. In this study, we hypothesized that the polyphenols, polypeptides, and oligosaccharides in Chinese rice wine can ameliorate diabetic cardiomyopathy (DCM) by altering gut microbiota and metabolites. Methods: Mice with DCM and high glucose cells were treated with rice wine polyphenols (RWPH), rice wine polypeptides (RWPE), and rice wine oligosaccharides. Cardiac function was evaluated by echocardiography and detection of myocardial injury markers. We observed the pathological structures using hematoxylin and eosin staining, Masson’s trichrome staining, and transmission electron microscopy. The expression levels of autophagy-related proteins and stubRFP-sensGFP-LC3 fluorescence were measured to evaluate autophagy. We performed TUNEL staining and measured the levels of Bax, Bcl-2, and p53 to assess apoptosis. To analyze the effects of the rice wine functional components on the gut microbiota and metabolites of DCM mice, we performed fecal 16S-rDNA gene sequencing and serum untargeted metabolomics. Results: Our results showed an increase in cardiac and mitochondrial function, promotion of autophagy, and inhibition of cardiomyocyte apoptosis, which indicates that RWPH and RWPE can ameliorate DCM. The abundance of Akkermansia and Desulfovibrio were reduced by the presence of RWPH and RWPE. The growth of the Lachnospiraceae_NK4A136_group and Clostridiales-unclassified were promoted by the presence of RWPH. Tryptophan metabolism-associated metabolites were increased and phenylalanine levels were reduced by the presence of RWPH and RWPE. The biosynthesis of primary bile acids was enhanced by the presence of RWPH. Conclusion: Both RWPH and RWPE provided a protective effect against DCM by promoting autophagy, inhibiting apoptosis, and reversing both gut microbiota dysbiosis and metabolic dysregulation.